Representasi Fisik Perempuan Dalam Antologi Puisi Catatan-Catatan Dari Bulan Karya Rieke Saraswati: Kajian Ginokritik Showalter - Indah Tri Widadari; Riki Nasrullah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to examine the physical representation of women based on gynocritical theory, as constructed through diction and figures of speech via stylistic analysis. This is a qualitative study employing a descriptive method. The data source for this study is the poetry anthology “Catatan-Catatan dari Bulan” by Rieke Saraswati, while the research data consists of quotations (containing diction and figures of speech) that represent the physical aspects of women. The data collection techniques used are documentation and note-taking. The documentation technique was used to identify primary data, namely the poetry anthology “Catatan-Catatan dari Bulan” by Rieke Saraswati, while the read-and-note technique was used to identify the diction and figures of speech that represent the physical aspects of women. The data analysis technique in this study is textual analysis through two approaches: stylistic analysis to dissect vocabulary and figures of speech, and gynocritical analysis to examine the physical representation of women. The findings reveal that the physical representation of women is constructed through vocabulary and figures of speech, including bodily anatomy, physiological conditions, and biological experiences. These findings confirm that female poets incorporate their unique experiences into the creation of literary works, which aligns with a central theory in gynocriticism, the physical experience of women.